Effects of Energy Price Fluctuations on Stock Return of Energy Companies in Indonesia: The Effect of Macroeconomic Variables and Subsidy Policy - Adhani, Ferenika; Nurazi, Ridwan (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study aims to analyze the effect of global energy price fluctuations, inflation, interest rates, exchange rates, and subsidy policies on stock returns of energy companies listed on the Indonesia Stock Exchange. The method used is panel data regression with the Fixed Effects Model (FEM) approach to capture unique characteristics between companies and simultaneous time variations. The results show that energy prices have a positive influence on stock returns, while inflation, interest rates, and exchange rates tend to have a negative impact. Energy subsidy policies also show a relevant relationship to the stock performance of energy companies. The findings provide insights for investors and policy makers in considering energy price dynamics and macroeconomic factors in investment strategies and energy sector policies in Indonesia.